Wind Energy Harvesting : Micro-to-Small Scale Turbines - Kishore, Ravi; Priya, Shashank; Stewart, Colin (De Gruyter Textbook, 2018)
This book provides the fundamental concepts required for the development of an efficient small-scale wind turbine. For centuries, engineers and scientists have used wind turbines of all shapes and sizes to harvest wind energy. Large-scale wind turbines have been successful at producing great amounts of power when deployed in sites with vast, open space, such as in fi elds or in offshore waters. For environments with limited space, such as dense urban environments, small-scale wind turbines are an attractive alternative for taking advantage of the ubiquity of wind. However, many of today's tools for aerodynamic design and analysis were originally developed for large-scale turbines and do not scale down to these smaller devices. Arranged in a systematic and comprehensive manner, complete with supporting examples, Wind Energy Harvesting: Micro- To Small-Scale Turbines is a useful reference for undergraduate and graduate level classes on energy harvesting, sustainable energy, and fl uid dynamics, and an introduction to the field for non-technical readers.